2009
DOI: 10.1091/mbc.e08-07-0786
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Induces Reversible Phosphatidylserine Exposure at the Plasma Membrane

Abstract: Cells normally undergo physiological turnover through the induction of apoptosis and phagocytic removal, partly through exposure of cell surface phosphatidylserine (PS). In contrast, neutrophils appear to possess apoptosis-independent mechanisms of removal. Here we show that Galectin-1 (Gal-1) induces PS exposure independent of alterations in mitochondrial potential, caspase activation, or cell death. Furthermore, Gal-1-induced PS exposure reverts after Gal-1 removal without altering cell viability. Gal-1-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 75 publications
1
76
0
8
Order By: Relevance
“…In contrast to our observations and those from other investigators, Matarrese et al (33) observed that Gal-1 sensitized human resting T lymphocytes to Fas-mediated cell death and that, at high doses, it was capable of inducing apoptosis in these primary cells. Discrepancies might reflect the different species used (human versus mouse), different protein preparations, or the method used to assess cell death, because phosphati-dylserine exposure is not necessarily associated with Gal-induced apoptosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our observations and those from other investigators, Matarrese et al (33) observed that Gal-1 sensitized human resting T lymphocytes to Fas-mediated cell death and that, at high doses, it was capable of inducing apoptosis in these primary cells. Discrepancies might reflect the different species used (human versus mouse), different protein preparations, or the method used to assess cell death, because phosphati-dylserine exposure is not necessarily associated with Gal-induced apoptosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…As the protective response evolves, perhaps as a requisite for eliciting specific signaling cascades (59), PrP C moves from lipid raft domains into the early endosome compartment. Simultaneously, the ATP-dependent enzyme aminophospholipid transferase, responsible for maintaining the normal membrane asymmetry of the lipid phosphatidylserine (60), is inhibited by lipid peroxidation (61), leading to increased expression of phosphatidylserine in the external leaflet of the plasmalemma, which is generally envisaged as an early marker of apoptosis (62), although other functional implications have been suggested (63,64). Surface expression of phosphatidylserine is not in itself sufficient to inevitably cause a cell to enter apoptosis (64), and surface expression of this moiety is reversible (65) and nonhomogeneous, with regions showing disproportionately higher concentrations (47), perhaps reaching the ratios used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the ATP-dependent enzyme aminophospholipid transferase, responsible for maintaining the normal membrane asymmetry of the lipid phosphatidylserine (60), is inhibited by lipid peroxidation (61), leading to increased expression of phosphatidylserine in the external leaflet of the plasmalemma, which is generally envisaged as an early marker of apoptosis (62), although other functional implications have been suggested (63,64). Surface expression of phosphatidylserine is not in itself sufficient to inevitably cause a cell to enter apoptosis (64), and surface expression of this moiety is reversible (65) and nonhomogeneous, with regions showing disproportionately higher concentrations (47), perhaps reaching the ratios used in our study. Once trafficked, the acidic pH of the early endosome would favor the loss of any histidine-bound copper associated with PrP C and concomitantly provide a milieu more favorable to the N-terminal binding to recently externalized phosphatidylserine, with this organelle shown to be enriched in this lipid and thereby offering a potentially important cationic protein sorting capacity (47).…”
Section: Discussionmentioning
confidence: 99%
“…When tolerance mechanisms fail, the cellular targets of immunity themselves can provide an additional layer of protection through resistance to effector mechanisms. Such cellular protection often reflects cell surface expression or release of soluble target cellderived factors that specifically modulate autoreactive cells (5)(6)(7), reducing the level of direct cell-mediated injury. Alternatively, some cell types have intrinsic resistance to the toxic effects of selfeffector molecules that otherwise potently destroy many pathogens (8).…”
mentioning
confidence: 99%